Mixed effects of a randomized trial replication study testing a cost-focused motivational intervention. (December 2022) - Rosenzweig, Emily Q.; Song, Yuchen; Clark, Shannon
Abstract: This study attempted to replicate a prior intervention study focused on reducing students' perceptions of cost to enhance their course performance. Undergraduate biology students ( N  = 147) were randomly assigned to complete a cost-focused intervention or a control condition. The intervention was designed to help students re-attribute their course challenges more adaptively, with a goal that this would help students perceive less cost associated with the challenges. Contrary to hypotheses, the intervention increased students' perceptions of cost at two time points. However, it also predicted higher scores on one of two course exams. Results demonstrate that cost-focused interventions may increase cost in some contexts, pointing to the context-specificity of intervention materials and the importance of replicating successful motivational interventions. However, results also suggest that increased cost does not necessarily correspond to lower academic performance in the context of an intervention aiming to help students re-appraise course challenges. Highlights: We conducted a pre-registered replication study of a prior cost-focused motivational intervention. Confirming hypotheses, the intervention promoted students' exam scores. Disconfirming hypotheses, the intervention increased students' perceptions of cost. Results point to the context-specificity of motivational interventions and the importance of replication.